2018
DOI: 10.5765/jkacap.2018.29.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Reveals Four Novel Loci for Attention-Deficit Hyperactivity Disorder in Korean Youths

Abstract: Attention-deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders, and affects 5-8% of children worldwide. 1) ADHD is associated with academic under-achievement and dysfunctional relationships with family members and peers. 2) It is a heterogeneous and complex disorder, and its pathophysiology remains largely unknown.Previous twin and adoption studies have suggested a strong genetic contribution to ADHD, and a meta-analysis of twin studies has reported an average heritabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In a mice model, MLIP is co-expression with PDE11A, a gene involved in social deficits of disorders of adulthood (including SCZ) ( Hegde et al., 2016 ). Moreover, the SNP rs9464011 in the intron of MLIP was significantly associated with attention-deficit/hyperactivity disorder in a family-based genome-wide quantitative trait loci analysis in a Korean population ( Kweon et al., 2018 ). Our results support the well-known pleiotropy of CNVs and once again demonstrate that some risk loci are shared by different neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In a mice model, MLIP is co-expression with PDE11A, a gene involved in social deficits of disorders of adulthood (including SCZ) ( Hegde et al., 2016 ). Moreover, the SNP rs9464011 in the intron of MLIP was significantly associated with attention-deficit/hyperactivity disorder in a family-based genome-wide quantitative trait loci analysis in a Korean population ( Kweon et al., 2018 ). Our results support the well-known pleiotropy of CNVs and once again demonstrate that some risk loci are shared by different neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these two chromosomes harbour important genes implicated in central nervous system development and body growth, including the FGFR2 gene. Lastly, Kweon et al (2018) carried out a genome-wide analysis on 135 ADHD subjects, revealing four quantitative trait loci comprising several promising candidates that could potentially be related to ADHD, inclusive of FGFR2. This is of interest if considered that our patient also received a co-diagnosis of ADHD (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…One other example of an association with PsychENCODE can be found in the CIDEA gene, which was identified by our study and was shown to be significantly down-regulated in ASD-affected individuals by PsychENCODE. Additionally, CIDEA has shown to be down-regulated in obesity and associated with ADHD, both of which often appear in tandem with ASD (Cortese & Vincenzi, 2012 ; Croen et al, 2015 ; Kweon et al, 2018 ; Lee & Ousley, 2006 ; Nordström et al, 2005 ). In total, the eQTLs described here are evidence of tissue-specific regulation across both brain and non-brain tissues.…”
Section: Discussionmentioning
confidence: 99%